2014
DOI: 10.1016/j.conbuildmat.2014.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of hygrothermal properties of wood-based products – Impact of moisture content and temperature

Abstract: Resumen-Mejorar el rendimiento térmico de los edificios mediante la adaptación del aislamiento puede reducir la pérdida innecesaria de calor y energía minimizando el impacto ambiental. El aislamiento térmico interior es a menudo el elegido en los edificios históricos para preservar sus características. Sin embargo, el aislamiento interior puede aumentar la acumulación de humedad en paredes que socavan su durabilidad. Hay una falta de conocimiento sobre la eficacia de sólidos muros históricos y el impacto del a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
84
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(93 citation statements)
references
References 28 publications
6
84
1
2
Order By: Relevance
“…A linear trend was observed, just the same as in Ref. [48] for wood-based materials, in Ref. [2] for earth bricks and in Ref.…”
Section: Materials Propertiessupporting
confidence: 56%
“…A linear trend was observed, just the same as in Ref. [48] for wood-based materials, in Ref. [2] for earth bricks and in Ref.…”
Section: Materials Propertiessupporting
confidence: 56%
“…For example, Tandiroglu [47] showed that the thermal conductivity of raw perlite aggregate concrete increases with temperature in the range from -10°C to +70°C. The increase of thermal conductivity with temperature was also observed on bio-based materials: Vololonirina [48] showed that the thermal conductivity of wood-based products scaled linearly with temperature between 10°C and 40°C.…”
Section: Thermal Propertiesmentioning
confidence: 76%
“…In the literature on the subject, there are very few publications describing sorption properties of boards made from annual plant waste which can be used as reference. The works published so far refer mainly to the sorption properties of wood, and as for wood-based material they deal with OSB and particleboards (Wu and Ren 2000;Hartley et al 2007;Moya et al 2009;Bonigut et al 2014;Mendes et al 2014 a, b;Vololonirina et al 2014;Derkowski et al 2015). However, based on the quoted literature and isotherms presented in Fig.…”
Section: Resultsmentioning
confidence: 99%